Raising College Access and Completion : How Much Can Free College Help? - Ferreyra, Maria Marta; Garriga, Carlos; Martin, Juan David; Sanchez Diaz, Angelica Maria (World Bank, Washington, DC, 2020)
Free college proposals have become increasingly popular in many countries, yet cross-country evidence indicates that higher college subsidies raise enrollment but not graduation rates. To capture the evidence and evaluate proposals, this paper develops and estimates a dynamic model of college enrollment, performance, and graduation. A central piece of the model, student effort, has a direct effect on class completion and an indirect effect mitigating the risk of performing poorly or dropping out. The model is estimated using rich student-level data from Colombia, and multiple free college programs are simulated. Among them, universal free college expands enrollment the most but does not affect graduation rates, thereby helping explain the evidence. Performance-based free college, in contrast, raises graduation rates yet has a smaller enrollment impact